Starspots as an Explanation for the Mysterious IYJ Continuum Excess Emission in Classical T Tauri Stars - Facundo Pérez Paolino; Jeffrey S. Bary; Lynne A. Hillenbrand; Madison Markham; William J. Fischer (The Astrophysical Journal)
An accurate estimation of the continuum excess emission from accretion spots and inner circumstellar disk regions is crucial for a proper derivation of fundamental stellar parameters in accreting systems. However, the presence of starspots can make disentangling the complicated multicomponent emission in these systems challenging. Subtraction of a single-temperature spectral template is insufficient to account for the composite stellar emission, as we demonstrated in a recent campaign involving weak-lined T Tauri stars. Here, we model the moderate-resolution near-infrared spectra of classical T Tauri stars, presenting new spectral models that incorporate spotted stars plus emission from accretion hot spots and a warm inner disk, allowing us to simultaneously reconstruct the entire 0.8–2.4 μ m spectrum of our 16 targets. Using these models, we re-derive the continuum excess emission. Our results indicate that accounting for starspots resolves the need to include a previously proposed intermediate-temperature component in the IYJ excess and highlights the importance of a proper treatment of starspots in studies of accreting low-mass stars.